2018
DOI: 10.1097/nur.0000000000000345
|View full text |Cite
|
Sign up to set email alerts
|

“It Just Is What It Is”

Abstract: Community health nurses should be aware of the positive and negative effects of living with these conditions to help build relationships and assist with condition management. Other implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Prior qualitative studies that have assessed the healthcare needs of women with IBS have identified themes related to the unpredictability of IBS symptoms and the impact of symptoms on multiple domains of daily life [33][34][35][36]. This is the first qualitative study to purposefully sample mothers with IBS to understand the impact on parenting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior qualitative studies that have assessed the healthcare needs of women with IBS have identified themes related to the unpredictability of IBS symptoms and the impact of symptoms on multiple domains of daily life [33][34][35][36]. This is the first qualitative study to purposefully sample mothers with IBS to understand the impact on parenting.…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative interview prompts were created by the study team based on principles of qualitative analysis [29] and prior literature [31][32][33][34][35][36] for the purposes of this study. Participants were asked: How long have you had IBS and abdominal pain and what has it been like for you?…”
Section: Methodsmentioning
confidence: 99%
“…One approach to understanding the symptom management needs of patients with IBS and concurrent symptoms of anxiety and/or depression is to conduct a qualitative study of their perspectives. Previous qualitative studies of the lived experiences and needs of those with IBS (Molinder et al, 2015;Parlar Kılıc et al, 2020;Skrastins & Fletcher, 2018) and a recently published systematic review of qualitative studies identified four themes of living with IBS: (1) physical, psychological and social consequences (which included anxiety and depression); (2) impact of IBS on working adults;…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…One approach to understanding the symptom management needs of patients with IBS and concurrent symptoms of anxiety and/or depression is to conduct a qualitative study of their perspectives. Previous qualitative studies of the lived experiences and needs of those with IBS (Molinder et al, 2015; Parlar Kılıc et al, 2020; Skrastins & Fletcher, 2018) and a recently published systematic review of qualitative studies identified four themes of living with IBS: (1) physical, psychological and social consequences (which included anxiety and depression); (2) impact of IBS on working adults; (3) dealing with IBS and (4) sources of support and support needs (Shorey et al, 2021). However, it is not clear from the review or the studies themselves how many participants had concurrent symptoms of anxiety and/or depression as this information was not reported (Shorey et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Among beverages, the participants mentioned alcoholic drinks, carbonated soft drinks, and acidic juices. Many of these foods and beverages overlap with triggers mentioned by people with IBS (Fletcher et al, 2008;Schneider et al, 2009;Skrastins & Fletcher, 2018). These triggers also overlap with foods containing higher quantities of FODMAPs (fermentable oligosaccharides, disaccharides, and polyols), which have been shown to trigger abdominal symptoms such as bloating, flatulence, abdominal discomfort, and diarrhea in, for example, IBS (Gibson & Shepherd, 2010).…”
Section: Coping Strategiesmentioning
confidence: 99%